Identification and characterization of phenolic compounds in hydromethanolic extracts of sorghum wholegrains by LC-ESI-MSn. (15th November 2016) - Kang, Jinguo; Price, William E.; Ashton, John; Tapsell, Linda C.; Johnson, Stuart
Highlights: More than 70 phenolic compounds in sorghum whole grain hydromethanolic extracts. Majority are reported for the first time in sorghum whole grains. Sorghum grains are rich in phenolic compounds. Phenylpropane glycerides and phenolamides found in all three sorghum samples. Abstract: Hydromethanolic extracts of brown, red, and white sorghum whole grains were analysed by LC-MS n in negative ESI mode within the range m/z 150–550 amu. Besides the flavonoids already reported in sorghum, a number of flavonoids were also identified in the sorghum grain for the first time, including flavanones, flavonols and flavanonols, and flavan-3-ol derivatives. Various phenylpropane glycerides were also found in the sorghum grain, the majority of them are reported here for the first time, and a few of them were detected with abundant peaks in the extracts, indicating they are another important class of phenolic compounds in sorghum. In addition, phenolamides were also found in sorghum grain, which have not been reported before, and dicaffeoyl spermidine was detected in high abundance in the extracts of all three type sorghum grains. These results confirmed that sorghum is a rich source of various phenolic compounds.